The Effect of Dadap Port Structure in Indramayu on Coastal Morphology - Muhammad Shodiq Supriyanto; Muhammad Cahyono; Eka Oktariyanto Nugroho; Dede Monarulhuda Sulaiman (Jurnal Teknik Sipil, 2023)
Abstract Human activities in coastal area will generally lead to a greater erosion rate due to the loss of natural protection or inappropriate structure. Dadap Beach, located at Juntinyuat District, Indramayu, West Java is one of the locations experiencing problems above. In 2003, a Fishing Port was built on Dadap Beach, with structure jutted 200 m from the shoreline to prevent sedimentation. However, currently there has been a massive sediment deposition in the port pool and behind the port. This study aims to determine the sedimentation pattern in Dadap Port, and the influence of the port structure on the coastal morphology, using a numerical model simulation. The results of this study indicate that the presence of the port structure has caused wave diffraction that forms a circulation flow behind the port structure and around the entrance area to the port pool, that lead to the formation of a tombolo behind the port and the sediment from the longshore currents and local scour enters the port pool area. Furthermore, the existence of Dadap port structure causes the obstruction of longshore currents so that the supply of sediment to the area around the port is reduced and the erosion rate is increasing. Keywords : Erosion, coastal morphology, numerical model. Abstrak Aktivitas manusia di wilayah pesisir umumnya akan menyebabkan bertambahnya laju erosi, yang disebabkan oleh hilangnya perlindungan alami atau pembangunan struktur yang tidak sesuai. Pantai Dadap yang terletak di Kecamatan Juntinyuat, Indramayu, Jawa Barat merupakan salah satu lokasi yang mengalami permasalahan di atas. Pada tahun 2003, dibangun Pelabuhan Perikanan di Pantai Dadap, dengan struktur menjorok 200 m dari garis pantai untuk mencegah sedimentasi. Namun, pada saat ini telah terjadi pengendapan sedimen yang masif di kolam pelabuhan dan di belakang pelabuhan. Studi ini bertujuan untuk mengetahui pola sedimentasi di Pelabuhan Dadap, dan pengaruh struktur pelabuhan terhadap morfologi pantai, dengan menggunakan simulasi model numerik. Hasil studi ini menunjukkan bahwa keberadaan struktur pelabuhan telah menyebabkan difraksi gelombang yang membentuk aliran sirkulasi di belakang struktur pelabuhan dan di sekitar area pintu masuk ke kolam pelabuhan, yang menyebabkan terbentuknya tombolo di belakang pelabuhan dan sedimen dari arus sejajar pantai dan gerusan lokal memasuki area kolam pelabuhan. Selain itu, keberadaan struktur pelabuhan Dadap menyebabkan terhambatnya arus sejajar pantai sehingga suplai sedimen ke daerah sekitar pelabuhan berkurang dan laju erosi semakin meningkat.. Kata-kata Kunci : Erosi, morfologi pantai, model numerik.